Evaluating the Clinical Reliability and Reference Values of the International Outcome Inventory for Cochlear Implants in the Department of Defense Population - Davidson, Alyssa; Boudin-George, Amy; Pillion, Elicia; Larionova, Nicole (Journal of the American Academy of Audiology, 2024)
Background Hearing loss significantly affects an individual's well-being, communication, social interaction, and quality of life. Cochlear implants serve as a viable management option. Given the variability in the impact of impairment, self-report measures are crucial for evaluating the perceived benefits of management options.Purpose The study aims to assess the reliability of the International Outcome Inventory for Cochlear Implants (IOI-CI) and establish evaluative cutoffs. This questionnaire evaluates patient's satisfaction with cochlear implants and contributes to the understanding of their experiences, addressing the increasing interest among cochlear implant clinicians.Research Design The design relies on electronic medical databases within the Veterans Affairs and Department of Defense systems. After identification of eligibility, recruitment was based on participants responding to mailed study documents. This research adopts a descriptive approach of the analysis of questionnaire responses as well as quantitatively evaluating the reliability.Study Sample Forty-nine service members, Veterans, and their dependents, including 32 men and 17 women, participated in the study. The participants had a mean age of 68.0 years, with cochlear implants ranging from 6 months to 2 years postinitial stimulation. The majority had a unilateral cochlear implant with a hearing aid on the contralateral ear.Data Collection and Analysis Data collected involved mailing baseline study packets, including the IOI-CI questionnaire, to potential participants identified through medical databases. Participants indicated consent by returning the study packet. Follow-up packets were sent at a later time. Intraclass correlation coefficients were utilized for test–retest reliability and generalized linear models (GLM) for exploring the impact of clinical and demographic factors. Data were analyzed using R.Results The ICC revealed a good level of agreement (ICC = 0.84) between baseline and follow-up assessments for the IOI-CI total score. The GLM did not identify significant factors influencing IOI-CI scores. Evaluative values were established, indicating total scores between 18 and 35 as within the range of general satisfaction with a cochlear implant for this questionnaire.Conclusion The study contributes valuable insights into the reliability of the IOI-CI and establishes evaluative cutoffs, aiding clinicians in assessing cochlear implant users' experiences and satisfaction.
Keywords: cochlear implants; surveys and questionnaires; consumer behavior